1997
DOI: 10.1017/s0033291797005679
|View full text |Cite
|
Sign up to set email alerts
|

Psychological preparedness for trauma as a protective factor in survivors of torture

Abstract: The study findings lend support to the role of prior immunization to traumatic stress and to unpredictability and uncontrollability of stressors in the effects of traumatization. Further research aimed at identifying the behavioural and cognitive components of psychological preparedness that play a role in traumatization may provide useful insights into effective treatment strategies for survivors of torture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(129 citation statements)
references
References 27 publications
(21 reference statements)
12
110
1
4
Order By: Relevance
“…In Nepal, continued affiliation with an armed group was associated with fewer mental health difficulties among former child soldiers . Similarly, previous research in Turkey has found that political affiliation protected against psychological problems in torture survivors (Basoglu et al, 1997). Despite consensus on participation in humanitarian response, a review of the international literature on children in emergencies only found anecdotal evidence to support it (Morris, Van Ommeren, Belfer, Saxena, & Saraceno, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In Nepal, continued affiliation with an armed group was associated with fewer mental health difficulties among former child soldiers . Similarly, previous research in Turkey has found that political affiliation protected against psychological problems in torture survivors (Basoglu et al, 1997). Despite consensus on participation in humanitarian response, a review of the international literature on children in emergencies only found anecdotal evidence to support it (Morris, Van Ommeren, Belfer, Saxena, & Saraceno, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…North et al (2002) speculated that psychological preparedness for dealing with gruesome aspects of firefighting may have been one variable fostering resilience among the men who worked at the Oklahoma bombing site. Similarly, Ba o lu, ş g Mineka, Paker, Livanou, and Gök (1997) reported that psychological preparedness for trauma buffers individuals against subsequent symptoms. These researchers found significantly lower rates of current PTSD among left-wing Turkish political activists who had been tortured by the military regime than among nonactivist Turks who had been arrested for nonpolitical crimes and tortured (18% vs. 58%).…”
Section: Risk Factors For Trauma Exposurementioning
confidence: 98%
“…Situational and event related dimensions of interest can be the sense of threat, the coping repertoire, or the type and extent of loss or change in living conditions [46, 47]. Finally, resilience must be taken into account, like sense of coherence, perceived invulnerability, or preparedness for a traumatic experience [48, 49, 50, 51]. …”
Section: Psychological and Etiological Modelsmentioning
confidence: 99%